1981
DOI: 10.1016/s0022-5347(17)55105-8
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Female Epispadias with Incontinence

Abstract: Six cases are described of congenital female epispadias and incontinence. Of these patients 3, who were seen in the last 4 years, were made continent by a 1-stage operation using a combined perineal and transvesical approach. The procedure includes excising the abnormally wide roof of the distal urethra from below narrowing the urethral caliber and mons plasty. From above the upper urethra and bladder neck are narrowed. Ureters are reimplanted if they have reflux or to facilitate bladder neck narrowing. The 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…This procedure, in combination with contouring of the mons pubis with puboplasty, resulted in the illusion of caudal recession of the vaginal introitus. Satisfactory cosmesis employing this surgical technique has been described in several surgical series [18,[67][68][69][70][71].…”
Section: Discussionmentioning
confidence: 98%
“…This procedure, in combination with contouring of the mons pubis with puboplasty, resulted in the illusion of caudal recession of the vaginal introitus. Satisfactory cosmesis employing this surgical technique has been described in several surgical series [18,[67][68][69][70][71].…”
Section: Discussionmentioning
confidence: 98%
“…Female epispadias has been described as a very rare condition, being 3-4 times less common than in males [2,[6][7][8]. It has also been suggested that mild degrees of epispadias are much rarer than more obvious forms, although there is no adequate explanation for this [7].…”
Section: Discussionmentioning
confidence: 99%
“…On inspection the bladder lining was visible through a patulous urethra, and direct pressure over the bladder caused a continuous stream of urine. Both ureters were re-implanted with an antireflux procedure and the urethral sphincter reconstructed, all uneventfully [2,5,6]. There was an improvement in continence but by 7 years old complete continence had not been achieved, and the dribbling had worsened.…”
Section: Casementioning
confidence: 99%
“…In three of the largest reported series, of a total of 26 cases there was not a single case presenting in adulthood, i.e. beyond puberty [1,3,4]. In developing countries such as India, where illiteracy and poverty are common and women have a low status in society, patients tend to hide their problem and suffer in silence, hence their late presentation.…”
Section: Discussionmentioning
confidence: 99%